Die Berechnung von Passport-Optionen mit Finiten Elementen - Jürgen Topper (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 1999)
– Except for special cases, passport option s do not have closed-form solutions. Here we show how to derive approximate solutions using finite element methods. We also show that finite elements offer advantages in computing the hedge parameters.
Keywords: C61; C63; G13; 330